Observation and confirmation of nine strong-lensing systems in Dark Energy Survey Year 1 data. Issue 1 (28th January 2020) - Nord, B; Buckley-Geer, E; Lin, H; Kuropatkin, N; Collett, T; Tucker, D L; Diehl, H T; Agnello, A; Amara, A; Abbott, T M C; Allam, S; Annis, J; et al.
ABSTRACT: We describe the observation and confirmation of nine new strong gravitational lenses discovered in Year 1 data from the Dark Energy Survey (DES). We created candidate lists based on (i) galaxy group and cluster samples, and (ii) photometrically selected galaxy samples. We selected 46 candidates through visual inspection and then used the Gemini Multi-Object Spectrograph(GMOS) at the Gemini South telescope to acquire a spectroscopic follow-up of 21 of these candidates. Through an analysis of these spectroscopic follow-up data, we confirmed nine new lensing systems and rejected two candidates, and the analysis was inconclusive on 10 candidates. For each of the confirmed systems, our report measured spectroscopic properties, estimated source image–lens separations, and estimated enclosed masses as well. The sources that we targeted have an i -band surface brightness range of i_SB 22\!-\!24 mag arcsec^-2 and a spectroscopic redshift range of z spec ∼ 0.8−2.6. The lens galaxies have a photometric redshift range of z lens ∼ 0.3−0.7. The lensing systems range in source image–lens separation from 2 to 9 arcsec and in enclosed mass from 10 12 to 10 13 M⊙ .